2014
DOI: 10.1352/1934-9556-52.6.456
|View full text |Cite
|
Sign up to set email alerts
|

Intersections Between the Autism Spectrum and the Internet: Perceived Benefits and Preferred Functions of Computer-Mediated Communication

Abstract: An online survey compared the perceived benefits and preferred functions of computer-mediated communication of participants with (N  =  291) and without ASD (N  =  311). Participants with autism spectrum disorder (ASD) perceived benefits of computer-mediated communication in terms of increased comprehension and control over communication, access to similar others, and the opportunity to express their true selves. They enjoyed using the Internet to meet others more, and to maintain connections with friends and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 47 publications
4
80
0
1
Order By: Relevance
“…Twitter use allows anonymity favoring the expression of people with real or perceived personal and/or or social restrictions [42]. The reported use of Twitter by transgender individuals and allies to discuss health and social needs supports this statement [43].…”
Section: Discussionmentioning
confidence: 95%
“…Twitter use allows anonymity favoring the expression of people with real or perceived personal and/or or social restrictions [42]. The reported use of Twitter by transgender individuals and allies to discuss health and social needs supports this statement [43].…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, they found people with ASD perceived many benefits to communicating online, such as "increased time to think and practice interacting" (Gillespie-Lynch et al 2014, p. 461), opportunities for self-expression, and opportunities to meet new people with similar interests or experiences. Additionally, people with ASD reported they found enjoyment in sharing experiences, writing blogs, and participating in discussion groups more so than those without ASD (Gillespie-Lynch et al, 2014). However, this same study also revealed that people with ASD found less enjoyment in using the Internet to keep in touch with family and friends and in accessing social networking sites compared to those without ASD (Gillespie-Lynch et al, 2014).…”
Section: Statement Of the Problemmentioning
confidence: 71%
“…Additionally, people with ASD reported they found enjoyment in sharing experiences, writing blogs, and participating in discussion groups more so than those without ASD (Gillespie-Lynch et al, 2014). However, this same study also revealed that people with ASD found less enjoyment in using the Internet to keep in touch with family and friends and in accessing social networking sites compared to those without ASD (Gillespie-Lynch et al, 2014).…”
Section: Statement Of the Problemmentioning
confidence: 71%
See 2 more Smart Citations